A review of solar compound parabolic collectors in water desalination systems. (2nd September 2020) - Mortazavi, Seyed Mostafa; Maleki, Akbar
ABSTRACT: The essential role of water in all the human being daily activities is undeniable, and the consumption of it by increasing the human life standards is increasing considerably. The shortage of drinkable water for people around the globe is becoming a very serious problem; therefore seawater desalination via renewable energy technologies like solar energy would be an environmentally friendly and favorable way to deal with the water shortage problem. Solar collectors by absorbing the solar radiation and converting it to thermal energy can directly be utilized for various applications like solar cooling systems which operate based on the solar absorption and adsorption of solar heating energy, the solar central power generation systems, solar desalination systems, solar water disinfection systems, etc. This article presents an overview on more-than-twenty-years research and development on applications of solar Compound Parabolic Collectors (CPCs) in desalination systems. As non-imaging and stationary collectors, CPCs by having relatively wide angle apertures receive the incoming solar radiation and reflect it to the absorber. It was perceived that CPCs are cost effective and useful for low-temperature applications (T < 100 ºC) and medium temperature range (100ºC < T < 250ºC) within which they are capable of being used in solar desalination systems and during recent years there has been an increasing tendency in using them in solar desalination systems.